2009
DOI: 10.1590/s1415-47572009005000076
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of the Monocelis lineata (Proseriata, Monocelididae) species complex assessed by phylogenetic analysis of the mitochondrial Cytochrome c Oxidase subunit I (COI) gene

Abstract: Monocelis lineata consists of a complex of sibling species, widespread in the Mediterranean and Atlantic Ocean. Previous genetic analysis placed in evidence at least four sibling species. Nevertheless, this research was not conclusive enough to fully resolve the complex or to infer the phylogeny/phylogeography of the group. We designed specific primers aiming at obtaining partial sequences of the mtDNA gene Cytochrome c Oxidase subunit I (COI) of M. lineata, and have identified 25 different haplotypes in 32 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The percentage of points in the network‐like areas (Schmidt et al., ) is in fact 0.2% for the 18S (Figure a) and 0.1% for the 28S (Figure b), well below the 20%–30% threshold reported by Schmidt and von Haeseler () as indicative of data sets not reliable for phylogenetic analyses. This is a relevant outcome, since, in the case of Proseriata, the number of genes/loci we could use is limited, as other specific primers, for example, for cytochrome c oxidase subunit I (COI) gene and other rDNA regions, developed for Proseriata, are useful only for few families (for details, see Sanna, Lai, Francalacci, Curini‐Galletti, & Casu, ; Casu, Sanna, et al., ; Scarpa, Sanna, et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of points in the network‐like areas (Schmidt et al., ) is in fact 0.2% for the 18S (Figure a) and 0.1% for the 28S (Figure b), well below the 20%–30% threshold reported by Schmidt and von Haeseler () as indicative of data sets not reliable for phylogenetic analyses. This is a relevant outcome, since, in the case of Proseriata, the number of genes/loci we could use is limited, as other specific primers, for example, for cytochrome c oxidase subunit I (COI) gene and other rDNA regions, developed for Proseriata, are useful only for few families (for details, see Sanna, Lai, Francalacci, Curini‐Galletti, & Casu, ; Casu, Sanna, et al., ; Scarpa, Sanna, et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Although these results provide strong reasons against using 18S for species delimitation, there are also difficulties associated with COI, which include high substitution rates, excessive saturation, biased substitution patterns, high AT content, and poorly conserved priming sites (15,17). These issues are known to reduce the efficacy of COI in certain meiofauna [e.g., nematodes (31) and proseriates (17)] and this may be one of the main reasons why COI has rarely been used for meiofaunal eDNA surveys (but see ref.…”
Section: Discussionmentioning
confidence: 99%
“…These issues are known to reduce the efficacy of COI in certain meiofauna [e.g., nematodes (31) and proseriates (17)] and this may be one of the main reasons why COI has rarely been used for meiofaunal eDNA surveys (but see ref. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Processes related to the different ecological features occurring in different areas greatly affect species from brackish‐water habitats, whose multifaceted and highly variable characteristics may enhance genetic differentiation among populations (Cognetti, ; Cognetti & Maltagliati, ). Several instances of species complexes in shallow and brackish waters have been found (Maltagliati et al ., ; Casu & Curini‐Galletti, , ; Sanna et al ., ; Virgilio et al ., ; Nygren & Pleijel, ). Nevertheless, different authors (Ayre et al ., ; Kelly & Palumbi, ) showed that the population genetic divergence in many coastal species was related to the potential for dispersal as well as habitat specificity.…”
Section: Discussionmentioning
confidence: 99%